The co-inoculation of Pseudomonas chlororaphis H1 and Bacillus altitudinis Y1 promoted soybean [Glycine max (L.) Merrill] growth and increased the relative abundance of beneficial microorganisms in rhizosphere and root - Zhang, Wentao; Mao, Guohao; Zhuang, Jiayao; Yang, Hao (Frontiers in Microbiology, 2023)
Currently, plant growth-promoting rhizobacteria (PGPR) microbial inoculants are heavily used in agricultural production among which Pseudomonas sp. and Bacillus sp. are two excellent inoculum strains, which are widely used in plant growth promotion and disease control. However, few studies have been conducted on the combined use of the two bacteria. The aim of this study was to investigate the effects of co-inoculation of these two bacteria on soybean [Glycine max (L.) Merrill] growth and physiological indexes and further study the effect of microbial inoculants on native soil bacterial communities and plant endophyte microbiota, especially microorganisms in rhizosphere and root. A pot experiment was conducted and four treatments were designed: group without any strain inoculant (CK); group inoculated with Pseudomonas chlororaphis H1 inoculant (J); group inoculated with Bacillus altitudinis Y1 inoculant (Y) and group inoculated with equal volume of P. chlororaphis H1 inoculant and B. altitudinis Y1 inoculant (H). Compared with CK, the three inoculant groups J, Y, and H exhibited improved soybean growth and physiological indexes, and group H was the most significant (p < 0.05). In terms of rhizosphere bacterial community structure, the relative abundance of native Luteimonas (9.31%) was higher in the H group than in the J (6.07%), Y (3.40%), and CK (5.69%) groups, which has potential value of disease suppression. Besides, compared with bacterial communities of the other three groups in soybean roots, group H increased the abundance of beneficial bacterial community for the contents of Allorhizobium-Neorhizobium-Pararhizobium-Rhizobium, Devosia, and Methylobacillus significantly increased (p < 0.05). In conclusion, we found that the composite inoculum of Pseudomonas chlororaphis H1 and Bacillus altitudinis Y1 could effectively promote soybean growth, increase yield and improve the beneficial bacterial community in root and rhizosphere and have certain value for soil improvement.